Wild and free: what are we conserving and how do we measure it? - Child, Matthew, author; Seiler, Jeanetta, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Saving a species from extinction is the minimum goal for conservationists. Ideally, we should conserve wild, flourishing, adaptive and self-sustaining populations. The IUCN recognises this ideal and states that only wild subpopulations can be considered for Red Listing. But what is wild? The absence of a measurable definition of wildness results in inconsistent Red Listing and thus inaccurate conservation progress reporting. As wildness exists along a spectrum from captive bred to completely free-roaming and many mammal species are subject to intensive breeding and production, which exist on a spectrum from purely commercial ranching to conservation orientated management, a framework that can unambiguously measure the conservation value or wildness of a subpopulation, regardless of the management system or philosophy is needed. Following two expert workshops, we designed a framework, comprising five variables relating to short-term subpopulation viability and four variables influencing long-term population resilience, to measure the species-specific wildness of subpopulations subject to varying management interventions. We used this framework to assess populations under various management systems and extrapolate adjusted Red List statuses for currently threatened species. The framework is a first attempt at providing a consistent and objective method to identify subpopulations that possess conservation value. As such, it will provide a foundation for policy-makers to provide different incentives to landowners focusing on biodiversity conservation versus commercial production. Importantly, developing an overall wildness status for our mammals, to complement their Red List status, will provide a holistic measure of conservation success rather than simply reporting risk of extinction.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.